a) 2x+7-3(x+4) = -4x-2(3-x)
2x+7 - 3x-12 = -4x-6+2x
x = -1
b) 4x+7+5(x+3) = 6x+1
4x+7+5x+15 = 6x+1
3x = -21
x = (-21):3 = -7
c) 4(x+3) -2x = 6-3(2-x)
4x+12 - 2x = 6 -6 + 3x
-x = -12
x = 12
d) 3(x-2)+2x-4 = 4(x+1) + 6
3x-6+2x-4 = 4x+4 +6
x = 20
e) 3(x-5)+5x -7 = 5(x+2) +1
3x-15+5x-7 = 5x+10+1
3x = 33
x = 33:3 = 11
f) 5(x+4)-3x+1 = 6(x+3) -9
5x+20 -3x+1 = 6x+18-9
-4x = -12
x = (-12):(-4) = 3
g) 5(x-3)+4x-6 = 4(x+3)-3
5x-15 +4x-6 = 4x+12 -3
5x = 30
x = 30:5 = 6
h) 7(x+2)+3x+6 = 4(x+5)-18
7x+14+3x+6 = 4x+20-18
6x = -18
x = (-18):6 = -3
i) 8(x+2)-2x+4 = 3(x+9)-13
8x+16-2x+4 = 3x+27-13
3x = -6
x = (-6):3 = -2
j) 9(x-2)-5x+7 = 4(x-3)+1
9x-18-5x+7 = 4x-12+1
4x-11 = 4x-11
x € |R